BARRIERS TO INDIVIDUALS ACCESSING PSYCHOLOGY SERVICES IN COMMUNITY HEALTH CENTERS - A QUALITATIVE STUDY INTO PSYCHOLOGISTS’ EXPERIENCES OF PROVIDING SERVICES TO PUSKESMAS OR COMMUNITY HEALTH CENTERS (CHCS) IN BANDA ACEH - Lely Safriana (Proceedings of AICS - Social Sciences, 2014)
Aceh was devastated by the 2004 tsunami with over 170.000 people killed along the coast of the Indian Ocean. Frankenberg et al. claims that in the wake of the tsunami post- traumatic stress disorders have manifested along Aceh’s coastal line. High rates. of psychopathology, including symptoms of anxiety, affective disorders, and post-traumatic stress symptom have been reported amongst survivors of the earthquake and tsunami in Aceh and Nias . Prior to the 2004 tsunami there existed a long running military conflict between the Aceh Separatist group (GAM) and the Indonesian government taking place between 1967 and 2004. This also had psychological impacts including depression, anxiety and trauma symptoms for the larger Acehnese community. Prior to the Tsunami 2004, there was little or no attention to mental health in the health system both nationally and locally. Mental health conditions following the Tsunami 2004 has brought opportunity for national and international agencies to initiate the establishment of a mental health care system. Mental health specialists have been limited in Aceh, although since the tsunami mental health training has been provided to the health department staff whose services are in primary care. In addition, to reach the community, mental health approaches based on community interventions have been established and funded by some agencies in terms of assessment and treatment or intervention. However, there continue to be substantial barriers to accessing mental health care in CHCs in Aceh. As international funding has declined, local initiatives between university and CHCs discontinued, psychology services continue to be stretched and those psychologists who provide these services do SOs on a voluntary capacity. This research has sought to develop understanding into the experiences of those volunteer psychologists who provide mental health care services in CHCs in Banda Aceh in order to gain knowledge for the improvement community mental health provision in Aceh. The design of this research is qualitative as this is considered the most appropriate method to address the research question that seeks an in depth understanding of the experiences and opinions of a small group of Clinical Psychologists working in Aceh Six clinical psychologists responded to an email advertisement forwarded through a clinical psychologist contact person in Aceh (see Appendix 1 for email advertisement) and participated in this study. The interviews were conducted in Indonesian language, recorded, transcribed verbatim in Indonesian and translated to English by the researcher. Each interview was of approximately 60 minutes duration. The semi-structured interview schedule was intended to explore these aspects of participants’ experiences. Data was analysed inductively, which is a “process of coding the data without trying to fit into pre-existing coding frame, or the researcher’s analytic preconceptions or called data-driven” This theme describes the community beliefs, stigma, taboo and perception toward mental illness and person with mental illnesses that prevent individuals and their family within the community in Aceh from accessing mental health services.